The declining role of post-treatment neck dissection in human papillomavirus-associated oropharyngeal cancer. (October 2020) - Daniels, Christopher P.; Liu, Howard Yu-hao; Bernard, Anne; Williams, Christopher; Foote, Matthew C.; Ladwa, Rahul; McGrath, Margaret; Panizza, Benedict James; Porceddu, Sandro Virgilio
Highlights: Large series of 418 node-positive HPV+ oropharyngeal cancer patients. Delayed PET-directed management of the neck following (chemo)radiation therapy. Low post treatment neck dissection rate of 4.5% without impairing disease control. Abstract: Background and purpose: Human papillomavirus-associated oropharyngeal cancer (HPV+ OPC) with regional lymph node metastases has a good prognosis following (chemo)radiation therapy (C/RT) but lymph nodes may remain detectable for several months. Delayed [ 18 F]-Fluorodeoxyglucose positron emission tomography/computed tomography (PET) can identify patients who may avoid post-treatment neck dissection (PTND). We investigated the rate of PTND in HPV+ OPC treated with C/RT and delayed PET-directed management of the neck. Materials and methods: This is a retrospective cohort study from a prospectively updated institutional database. Eligible patients were treated between January 2005 and July 2017 with a minimum of 18 months follow up, had node-positive, non-distant metastatic HPV+ OPC and were treated with RT (70 Gy/35#/5 per week) with concurrent Cisplatin or Cetuximab, or accelerated RT alone (68 Gy/34#/6 per week). The primary endpoint was rate of PTND. Secondary endpoints were locoregional failure free survival (LRFFS), regional failure free survival (RFFS), distant metastatic failure free survival (DMFFS), overall survival (OS) and oropharyngeal cancer-specific survival (CSS). Results: 418 patients were eligible. Nineteen patients (4.5%) received a PTND. None of the tested variables were associated with an increased risk of PTND. Five-year probabilities for LRFFS, RFFS, DMFS, OS and CSS were, 91.2% (95% CI 88.3–94.2), 93.4% (95% CI 90.8–96.0), 91.2% (95% CI 88.3–94.2), 86.4% (95% CI 83.0–90.1) and 90.2% (95% CI 87.1–93.4), respectively. Conclusion: In a large cohort with good median follow up and protocolized C/RT, delayed PET-directed management of the neck affords a lower rate of PTND than reported in historical series without compromising disease control and survival.